A Comparison of Methods for Platelet Lysis and the Isolation of Platelet Membranes - Barber, A. J; Pepper, D. S; Jamieson, G. A (Thrombosis and Haemostasis, 1971)
Four methods of platelet lysis, namely, sonication, nitrogen cavitation in a high pressure bomb, the use of a “no clearance” tissue homogenizer and simple osmotic lysis have been compared in terms of ease, effectiveness and reproducibility in comparison with a method involving the hypotonic lysis of glycerol-loaded platelets ; the most extensive studies have been carried out using sonication and the tissue homogenizer. In order to reduce the degree of fragmentation of the platelet membrane, the use of surface stabilizing agents such as zinc chloride and fluorescein mercuric acetate have also been investigated. Membranes obtained in these different ways have been isolated by centrifugation on continuous or discontinuous sucrose density gradients and the resulting fractions compared by electron microscopy, enzymatic activity, chemical analysis and hemagglutination inhibition. The glycerol-lysis technique was found to be most effective (85%) in untreated platelets and the degree of lysis was considerably reduced in platelets hardened by the zinc chloride method. Ultrastructural studies showed that the largest membrane fragments (175 nm) were obtained by glycerol lysis of untreated platelets and that smaller vesicles (50-100 nm) were obtained by the other techniques even following membrane stabilization. Double membrane structures were obtained in several of these methods.